Back Cover: Electric‐Circuit Simulation of Quantum Fast Hitting with Exponential Speedup (Adv. Quantum Technol. 4/2022). Issue 4 (7th April 2022) - Zhang, Hanxu; Chen, Tian; Pan, Naiqiao; Zhang, Xiangdong
Abstract : In article number 2100143, Hanxu Zhang, Tian Chen, Naiqiao Pan, and Xiangdong Zhang implement the simulation of a quantum fast hitting algorithm in an electric circuit. The motion equations of the circuit are Schrödinger‐like. The theoretical and experimental results in the circuit reveal that, the success probability at the arriving time is in the order of 1/n for the n‐order unbalanced tree, which displays the quantum advantage.